Α-Thalassemia Mutations in Ilam Province, West Iran. (4th May 2022) - Moradi, Keivan; Aznab, Mozaffar; Azimi, Azam; Biglari, Mostafa; Shafieenia, Samaneh; Alibakhshi, Reza
Abstract: Despite several studies performed in different provinces of Iran to identify the spectrum of α-globin gene mutations, no such study has so far been carried out in Ilam Province. A total of 274 individuals, including 201 α-thalassemia (α-thal) carriers and 73 normal subjects, originating from the northern counties of Ilam Province, participated in this study. Analysis of α-globin defects was performed using multiplex gap-polymerase chain reaction (gap-PCR), amplification refractory mutation system (ARMS)-PCR and direct sequencing, which revealed a total of 11 different mutations and 22 different genotypes. The –α 3.7 (rightward) (NG_000006.1: g.34164_37967del3804), α −5 nt α ( HBA2 : c.95 + 2_95 + 6delTGAGG), and –α 4.2 (leftward) deletions were the most prevalent mutations identified in our study, with frequencies of 66.23, 10.09 and 8.33%, respectively. In conclusion, the present study showed that the α-thal mutation spectrum in Ilam Province, at least in the northern part of the province, is different from that in other geographical regions of Iran. These results increase our knowledge about the spectrum and distribution of α-globin gene mutations in Iran.